The impact of a change in sovereign credit ratings on stock market volatility: A comparison of emerging and developed countries - Govender, Sharlene (African Inst. of Fin. Markets and Risk Mngnt, 2018)
Sovereign credit ratings affect a country’s financial well-being. The financial markets, at large, have become quite topical within the public space, as well as policy makers and academics. This area has been examined in detail, especially after the global financial crisis of 2008. Rating agencies have been under great scrutiny against their issued ratings and accused of favouring developed economies over developing ones by providing higher ratings to the former. Using a panel of emerging and developed countries over a period of ten years (June 2007 – June 2017), this study examines whether a change in sovereign credit ratings by one of the big three rating agencies has an effect on the volatility of the stock market. This dissertation makes use of an event study over various estimation windows, and the findings depict that changes in sovereign credit ratings do have an effect on stock market volatility. Rating downgrades tend to increase volatility whilst upgrades tend to decrease volatility. Countries that have lower ratings, classified as emerging economies, are no less sensitive to rating changes compared to developed markets and both observe a significant effect on volatility when there is a change in credit ratings. The credit rating agency that had the greatest impact on the volatility of the stock market in response to a rating change is S&P. This was for both upgrades and downgrades. Fitch and Moody’s did not elicit any significant findings. This shows that the market is more responsive to an announcement by S&P than the other agencies. An understanding of the actual effect of this volatility in the equity stock market will have implications for investors, governments, pension funds and asset holders by providing them with country risk assessments and giving them the ability to rebalance their portfolios as required. It also has an impact in determining the cost of capital and evaluating investments, which affect asset allocation decisions. This study has important information, which could help contribute to credit rating agencies’ understanding of the implications that their issued ratings have on the stock market and their contribution to volatility within the market place. The policy implications of this study could affect institutions, especially the Basel committee and banking institutions whom are highly affected by the policies set out by Basel.